A Conceptual Framework of Sustainability Balanced Scorecard to Enhance the Performance of Shared Service Centre - Ali, Agha Shadab; Maelah, Ruhanita; Meerani, Mufeed Ahmed; Jantan, Mohd. Dan (Asian Journal of Accounting Perspectives, 2022)
Research aim: The paper aims to propose a conceptual framework of a sustainability balanced scorecard that communicates the requisite of SSCs along with aggregation of the three dimensions of Triple Bottom Line (People, Planet, and Prosperity) and four perspectives of the Balanced Scorecard (Financial, Customer, Internal Business, and Innovation and Learning) to the assess appropriate performance indicators and sustainability approach on the management dashboard at SSC. Design/ Methodology/ Approach: This conceptual study is based on a review of prior literature on sustainable performance management in SSCs and in-depth interviews with SSC executives to assess the performance indicators for enhancing corporate sustainability. Research finding: The proposed research framework is a combination of several perspectives of BSC and facets of TBL such as customer, internal business innovation and learning, economy, environment, and social. Theoretical contribution/ Originality: The paper proposed a conceptual framework of sustainable performance management at the organisational level, especially in the shared service industry that can also be applied for future academic research. Practitioner/ Policy implication: The proposed framework may generate new insights for the policymakers and practitioners to guide the practices to strategically refine for effective management dashboards in the shared service industry. Keywords: Balanced Scorecard (BSC), Performance Management, Shared Service Centre (SSC), Sustainability, Sustainability Balanced Scorecard (SBSC) Type of article: Conceptual paper JEL Classification: M14, M21